Evaluating the Impact of Fish Silage on Cyst Production and Larval Quality in Aquaculture Hatcheries: A Nutritional and Growth Performance Analysis - Fransiskus Rumapea (Jurnal Ilmu Pendidikan dan Humaniora, 2024)
Aquaculture hatcheries play a crucial role in providing sustainable seed supply for aquaculture operations, with cyst production and quality being fundamental factors influencing their success. This research aimed to assess the impact of fish silage, a fermented fish product, on cyst production and quality in aquaculture. The study involved evaluating cyst yield, size, viability, nutritional composition, and growth performance parameters of cysts derived from fish fed with fish silage-based diets compared to conventional feeds. Findings revealed that fish silage-fed fish exhibited significantly higher cyst yields, larger cyst sizes, and superior cyst quality, characterized by higher viability rates and hatching success. Nutritional analysis showed that cysts derived from fish silage-fed fish had higher protein, lipid, and essential fatty acid content. Additionally, larvae hatched from cysts derived from fish silage-fed fish demonstrated better growth performance parameters. These results suggest that fish silage positively influences cyst production and quality in aquaculture through mechanisms involving nutritional composition, microbial activity, and physiological responses. The implications of these findings for aquaculture practices include the potential use of fish silage as a valuable feed ingredient to enhance reproductive performance, cyst yield, and larval quality.